Thrill of the chase - Nolan, Kathryn (Entangled, 2025)
Reporter Harper Hendrix is chasing a career-making story -- and the legendary Blackburn Diamonds are her ticket to the top. She's smart, ambitious, and definitely not distracted by the infuriatingly hot antiques salvager standing in her way. Eve Bardot has spent years searching for the diamonds, and she's not about to let a pesky, too-charming reporter ruin her shot. But when rival treasure hunters close in, Eve and Harper strike an uneasy truce to track down the prize together. Their partnership? Purely strategic. The bickering? Nonstop. The chemistry? A complete disaster. As clues pile up and tension turns explosive, Harper and Eve must decide what's more dangerous: the hunt... or falling for each other.